Total Synthesis of (±)-Spirobenzofuran - Su, Hang; Zhou, Ting; Liu, Bo (Synlett, 2013)
Spirobenzofuran, embracing a cyclopentane-spirofused benzofuran carbon framework, was efficiently assembled via semipinacol rearrangement with Me3Al from 2,5-dimethoxy-4-methylacetophenone.
Keywords: spirobenzofuran; semipinacol rearrangement; trimethylaluminium; total synthesis; sesquiterpenoid